Validity, reliability and factor analysis of the Serbian version of Kogan‘s attitude towards old people scale - Adamović, Milosav; Bar, Zoran; Todorovic, Vojislav (Sociološki pregled, 2022)
Introduction. As the number of older persons continues to increase, there is a need to validate a reliable instrument to examine attitudes towards this population in Serbia. This research aimed to examine the validity and reliability and to determine the factor structure, that is, to adapt the Serbian version of the Kogan‘s Attitude towards the Old People scale. Method. The research was conducted on a planned sample of 321 respondents, students of social science and humanities, mostly gathered in the territory of Belgrade and Novi Sad. Results. Achievements at the level of the whole scale ranged from 67 to 121 (M = 100, SD = 7.83).The obtained Content Validity Index (CVI = 0.90) indicated a high level of validity in this assessment domain. The Cronbach‘s alpha Coefficient of reliability for items given in a positive connotation was α = 0.77, while slightly higher value was obtained for the items given in a negative connotation (α = 0.83). At the level of the entire instrument, after recoding the inversely defined items, the value α = 0.88 was calculated, indicating a high level of reliability of the scale used. Except for item 13, statistically significant correlation (p
Keywords: Kogan‘s scale; attitudes; elderly persons